Análisis y prevenciones en torno a las reformas de la Constitución en Chile - Núñez Leiva, J. Ignacio (2023)
This article studies the current stage of constitutional law in Chile. Starting with an apparent constitutional malaise, this paper attempts to define the importance of the Constitution today, as well as some conflicts that arise with constitutionalism. The author proposes criteria that would temper the effects of such conflicts. Even though the author focuses on the situation in Chile, the article contains ideas and a reasoning of universal scope.